Study of Fethullah Gulen's Thought for The Development of Multicultural Islamic Education in Indonesia - Sutrimo Purnomo (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
Conflicts that occur in Indonesia, such as the free aceh movement, the republic of South Maluku or even among fellow Islamic organizations provide an illustration as well as a sign of how fragile the multicultural-based national construction in Indonesia is. If this continues and does not receive serious attention, the integrity of the Unitary State of the Republic of Indonesia will be at stake. For this reason, awareness of the importance of multiculturalism needs to be instilled, among others, through education, including multicultural Islamic education. This paper aims to analyze Fethullah Gulen's thoughts on multicultural Islamic education and its integration for the development of multicultural Islamic education in Indonesia. This research is a type of qualitative research which is library research with content analysis as a research approach with primary sources in the form of Gulen's writings entitled Toward a Global Civilization of Love and Tolerance and supported by several related books and scientific articles as secondary sources, including books entitled Multicultural Education: Issues and Perspectives written by James A. Banks. The results of the research show that Gulen's thoughts have colored and become an inspiration for world life. Life is often decorated with disharmony and even violence and chaos caused by a poor attitude of respect and appreciation for sunnatullah in the form of diversity and multiculturalism. It is here that Gulen offers a solution to overcome these problems through love, dialogue and tolerance. This love, dialogue and tolerance can become principles and references for the development of multicultural Islamic education in Indonesia in order to produce a young generation of Indonesian Muslims who have an attitude and spirit of respect and appreciation for differences and diversity so as to create a safe and peaceful country.